Current status and future trends of seismic prediction and assessment technology for coalbed methane reservoirs - Haibo WU; Pingsong ZHANG; Shi’ang XU; Yaping HUANG; Shouhua DONG; Yan CHENG; Donghui LI; Sheng ZHANG; Min ZHANG (Meitian dizhi yu kantan)
Background The seismic prediction and assessment technology for coalbed methane (CBM) reservoirs has undergone rapid development for over three decades, playing an indispensable role in CBM exploration. Methods This study reviews the development history and current status of core technologies within the seismic prediction and assessment technical system for CBM reservoirs, including seismic-petrophysical tests, modeling and inversion, seismic wavefield simulation, seismic amplitude versus offset (AVO) inversion and seismic attribute inversion, and integrated seismic prediction of the sweet spot areas of CBM reservoir resources and engineering. Furthermore, this study delves into the impacts and limitations of the characteristics of CBM reservoirs, such as adsorbed gas, pore-fracture dual system, viscoelasticity, and thin layers, on the accuracy and resolution of seismic prediction and assessment technology for CBM reservoirs. Finally, this study proposes future prospects for the development trends and directions of seismic prediction and assessment technology for CBM reservoirs from two perspectives: the shift in the targets for CBM reservoir exploitation and the technological iteration of critical seismic exploration links. Prospects In the future, seismic prediction and assessment technology for CBM reservoirs will closely follow the development direction of deep CBM exploitation and the multi-gas commingling production from coal measures. Breakthroughs are to be achieved in the following technical aspects: fine-scale petrophysical characterization of reservoirs, numerical modeling and simulation, high-precision exploration data acquisition, target-oriented fine-scale processing, multi-parameter high-precision intelligent inversion, and comprehensive identification of sweet spot areas. This will promote a leap forward in the field of CBM exploration.